Injuries and Contusions in Recreational and Sports Horse Riding - Rena Majchrowicz; Karolina Karaś; Piotr Matłosz; Jarosław Herbert (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
Horse riding is a satisfying and exciting sport and recreation activity. However, it is not without risk. A large percentage of riders experience accidents of varying degrees of severity during their professional and recreational careers. Any injury, even one that appears to be harmless, may turn out to be serious and exclude a competitor from sport for a long period of time. The purpose of the following research was to analyse the presence and incidence of contusions and injuries among novice and professional riders. The material for this study was collected using a research questionnaire conducted on a group of 1973 people. Participants were chosen at random and belonged to an equestrian community from different age groups. The research was carried out all over Poland. Equestrianism is definitely an injurious physical activity, which is confirmed by the answer of 75% of respondents who consider this sport to have been harmful and have suffered an injury related to horse riding. Most respondents suffered hand contusions (45.5%), concussion (25.4%) and hand fractures (16.4%). The strength of the study was the number of respondents (1973) and feedback on, among others, various types of injuries. These injuries can be easily avoided due to increased knowledge, practice, and education.